Talk is cheap, text is cheaper [mobile messaging]. - Cherry, S.M.
E-mail was the first killer application for the Internet-now messaging is coming to cellphones. How does a software application go from zero to 100 million users in a couple of years? One way is to be built into Windows. Another is for the world's largest cellphone manufacturers to make it a standard. That has not happened yet, but it's about to. Three titans of the mobile world, Nokia, Motorola, and Ericsson, are behind a developing standard for instant messaging (IM) between cellphones. Called Wireless Village, it was approved in February as Draft 1.0 by a consortium that includes more than 150 equipment manufacturers, and could be implemented in new cellphones by early fall. Meanwhile, a slightly different messaging mode, short message service (SMS), has already crossed the Atlantic from Europe. In recent months, the leading US wireless carriers have started to promote the service. This could be good news for investors and for the carriers themselves-so good, in fact, that it is said the abbreviation really stands for "significant money streams". European mobile carriers are reporting that SMS accounts for as much as 9 percent of revenues and 20 percent of profits
Keywords: Wireless Village; Cellphones; Instant messaging; Short message service